"At Variance with Accepted Practice:" Antiracist Pedagogies within the Jewish History Museum. (2nd October 2019) - Davis, Bryan L.; Goldberg, Ariel
ABSTRACT: At the Jewish History Museum and Holocaust History Center in Tucson, Arizona, photographs, text, and audio displays present Jewish histories alongside local histories of African-American, Latinx, and Native peoples – among others – in Southern Arizona, where Jews comprise only 2–3% of the population. In documenting our pedagogical tools for presenting these histories, we ask what forms of responsibility and context are necessary when engaging antisemitism and other forms of exclusion. What does it mean to present these histories and not romanticize or isolate them in the past, but instead instrumentalize them in order to prompt contemporary action? Weekly public talks and an education program that reach several thousand students a year employ antiracist pedagogical methodologies for facilitating difficult conversations inside the museum. This article will document our frameworks of discussion and lines of questioning prompted by our museum displays that actively thematize race and institutional forms of discrimination.